2020
DOI: 10.1111/eje.12610
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between European postgraduate programme accreditation and national research output: The case of the Network of Erasmus‐Based European Orthodontic Postgraduate Programmes (NEBEOP) in orthodontics. A bibliometric study

Abstract: Aims To assess in each European country the correlation between the number of Network of Erasmus‐Based European Orthodontic Postgraduate Programmes (NEBEOP) members and orthodontic research activity. Secondary objectives were to describe and quantify Europe's orthodontic research. Materials and methods Articles published between 2014 and 2018 in 4 major orthodontic journals (American Journal of Orthodontics and Dentofacial Orthopedics, European Journal of Orthodontics, The Angle Orthodontist, Orthodontics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The availability to make a master's degree affects not only the quality of education and research as has been reported [ 8 ], but the stability of the dental market and the number of people in a particular specialty. The chosen institutions (Universities, Health Ministry, official colleges and councils, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability to make a master's degree affects not only the quality of education and research as has been reported [ 8 ], but the stability of the dental market and the number of people in a particular specialty. The chosen institutions (Universities, Health Ministry, official colleges and councils, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for specialized dental care for various reasons, especially to improve the quality of treatment and patient safety [ 7 ]. Postgraduate education is also associated with higher research activity [ 8 ]. However, it is necessary to expand dental specialist training to conform with common standards for specialist education [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 The favorable effects of specialty program accreditations like the Network of Erasmus‐Based European Orthodontic Postgraduate Programs could also elucidate the high number of orthodontic studies produced by academic institutions. 25 …”
Section: Discussionmentioning
confidence: 99%